Freshwater pond microalgae for biofuel: Strain isolation, identification, cultivation and fatty acid content - Bayu Afnovandra Perdana; Abdi Dharma; Indra Junaidi Zakaria; Syafrizayanti SYAFRIZAYANTI (Society for Indonesian Biodiversity, 2021)
Abstract. Perdana BA, Dharma A, Zakaria IJ, Syafrizayanti. 2021. Freshwater pond microalgae for biofuel: Strain isolation, identification, cultivation, and fatty acid content. Biodiversitas 22: 505-511. Microalgae have capability to produce fatty acid for biofuel, drugs, and nutraceutical foods development. This study was carried out to obtain a new strain candidate for fatty acid production. The methods were used in this study include isolation of microalgae species from freshwater ponds of Andalas University, Padang, Indonesia. Molecular identification of microalgae was carried out with specific 18S rRNA primer, F-P73, and R-P47. Microalgae growth was measured by cell density and optical density method using various wavelengths (400, 500, and 680 nm). Total lipid was extracted using Bligh & Dyer method. Fatty acid analyses were conducted using gas chromatography-mass spectroscopy. Microalgae were isolated i.e Chlorella emersonii MAUA001, Mychonastes rotundus MAUA002, Scenedesmus dimorphus MAUA003, and Scenedesmus armatus MAUA004. The result exhibited M. rotundus was the highest lipid content, it was about 28.8% biomass weight. Fatty acid profiles of microalgae were dominated by monounsaturated (MUFA) and saturated fatty acid (SFA). The highest content of fatty acid species found in C. emersonii with octadecenoic acid (C18:1) was 47.74% total lipid. This work showed that C. emersonii has potential as biodiesel due to high saturated fatty acid.